Places in the Architecture of Machado and Silvetti - Mark Pasnik (Oz, 1997)
The strategies of placemaking developed during the late seventies and implemented in the early eighties have proven insufficient to grapple with many of the irregularities of the contemporary metropolis. So while contextualism, collage, and other formalist design tools have been viable means for architects to reintegrate the fabric of pedestrian cities, such a fabric simply never existed in many American cities, particularly at their periphery. Ed. note: The featured project is by Machado and Silvetti Associates.